ANALISIS NILAI TUKAR SUBSISTEN DAN TINGKAT KESEJAHTERAAN PETANI CABAI MERAH KERITING DI DESA TRIMULYO KECAMATAN TEGINENENG KABUPATEN PESAWARAN - Fitri Aisyah Nur Alimah; Ali Ibrahim Hasyim; Sudarma Widjaya (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purposes of this research are to analyze farming income curly red chili, subsistence exchange rate of curly red chili, and the welfare of curly red chili farmers in the Trimulyo Village, Tegineneng Subdistrict, Pesawaran Regency. This research uses a survey method. The samples of the study are 60 farmers who are active in the farmer groups and determined using simple random sampling. Farming income curly red chili is analyzed using Revenue Cost Ratio (R/C ratio). The subsistence exchange rate is analyzed by dividing the revenue of curly red chili farming with total expenditure of farmers respondent. The welfare of farmers is analyzed using household exchange rate income farmers. The result of the research shows that curly red chili farming is profitable and feasible to continue. The income of curly red chili farming gives a significant contribution to household expenditure. The farmer household income exchange rate is relatively high, therefore, the farmer household is in prosperous category.Key words: curly red chili, exchange rate, income, welfare